2009
DOI: 10.21101/cejph.a3508
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Association between Air Pollution and Emergency Room Admissions for Chronic Obstructive Pulmonary Disease in Niš, Serbia

Abstract: The present study assesses the short-term association between black smoke (BS) and sulphur dioxide (SO 2) levels in urban air and the daily number of emergency room admissions for chronic obstructive pulmonary disease (COPD) in Niš, Serbia. Generalised linear models extending Poisson regression were fitted controlling for time trend, seasonal variations, days of the week, temperature, relative humidity, air pressure, precipitation, rainfall, snowfall, overcast, and wind velocity. The emergency room admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…With different exposure units used, the percent increase for particles in these studies was from 0.74 in a study conducted by Qiu et al 106 in Hong Kong, People’s Republic of China, to 18.6 in a study conducted by Arbex et al 104 in São Paulo, Brazil. When the same exposure unit of 10 µg/m 3 was used, five studies 97 , 100 , 103 , 105 , 106 showed a range of percent increase from 0.74 in Hong Kong, People’s Republic of China, 106 to 4.3 in São Paolo, Brazil, 100 with an average of 2.19 ( Figure 3B ). This is similar in magnitude to that in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…With different exposure units used, the percent increase for particles in these studies was from 0.74 in a study conducted by Qiu et al 106 in Hong Kong, People’s Republic of China, to 18.6 in a study conducted by Arbex et al 104 in São Paulo, Brazil. When the same exposure unit of 10 µg/m 3 was used, five studies 97 , 100 , 103 , 105 , 106 showed a range of percent increase from 0.74 in Hong Kong, People’s Republic of China, 106 to 4.3 in São Paolo, Brazil, 100 with an average of 2.19 ( Figure 3B ). This is similar in magnitude to that in high-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of black smoke were found in Serbia (Milutinović et al, 2009), increasing concentrations of SO 2 were noticed in Prague (Duben, 1988). In Greece, a study that investigated the gas concentration evolution along the year indicated the powerful influence of the season on the air pollutant levels, being minimal in summer and maximal in winter (Papaioannou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Also, epidemiological studies have shown that exposure to ambient levels of air pollution is associated with clinical and histological changes of the eye [10,11]. Previous studies on the impact of air pollution on the health of the Serbian population have mostly concerned respiratory, cardiovascular, and hematopoietic systems [12][13][14]. Ours is the first study in our country that deals with the impact of ambient air pollution on the eye.…”
Section: Introductionmentioning
confidence: 99%